Pengaruh Sumber Dan Dosis Pupuk Kalium Terhadap Pertumbuhan Tanaman Jagung Manis (Zea mays L. saccharata) Varietas Paragon - pradita prima deviyanti; Anis Rosyidah; Siti Muslikah (AGRONISMA, 2022)
The element K is the second macro nutrient after N which is most widely absorbed by plants. The use of K fertilizer with the right dose is an effort to increase plant growth and yield. This study aims to study the effect of various sources and doses of K fertilizer on the growth of paragon variety of sweet corn. The design used was split plot design with control consisting of main plots and subplots. The main plot is the source of K fertilizer which consists of 2 levels (KNO3 and K2SO4). Sub-plots were dosed with K fertilizer consisting of 4 levels (50 kg ha-1, 100 kg ha-1, 150 kg ha-1 and 200 kg ha-1) and added with the control treatment. The results showed that the application of various sources and doses of K fertilizer affected plant height, number of leaves, leaf area, leaf area index, leaf chlorophyll content and time of emergence of male flowers. The application of KNO3 fertilizer at a dose of 150 kg ha-1 resulted in the best growth of paragon variety of sweet corn.Â Keywords : source and dose of K fertilizer, sweet corn, growth, paragon variety